(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the main linguistic stereotypes faced by migrant children, such as "foreign accent," "language deficiency," and biases towards bilingualism. The study explores their impact on academic performance, social integration, and self-identity. Special attention is given to educational policies and the role of society in overcoming these stereotypes. The article also discusses strategies aimed at creating an inclusive educational environment and supporting migrant children.